Te-based chalcogenide materials for selector applications - A. Velea (Nature Portfolio, 2017)
Abstract The implementation of dense, one-selector one-resistor (1S1R), resistive switching memory arrays, can be achieved with an appropriate selector for correct information storage and retrieval. Ovonic threshold switches (OTS) based on chalcogenide materials are a strong candidate, but their low thermal stability is one of the key factors that prevents rapid adoption by emerging resistive switching memory technologies. A previously developed map for phase change materials is expanded and improved for OTS materials. Selected materials from different areas of the map, belonging to binary Ge-Te and Si-Te systems, are explored. Several routes, including Si doping and reduction of Te amount, are used to increase the crystallization temperature. Selector devices, with areas as small as 55 × 55 nm2, were electrically assessed. Sub-threshold conduction models, based on Poole-Frenkel conduction mechanism, are applied to fresh samples in order to extract as-processed material parameters, such as trap height and density of defects, tailoring of which could be an important element for designing a suitable OTS material. Finally, a glass transition temperature estimation model is applied to Te-based materials in order to predict materials that might have the required thermal stability. A lower average number of p-electrons is correlated with a good thermal stability.